2009
DOI: 10.1098/rsif.2009.0322
|View full text |Cite
|
Sign up to set email alerts
|

Placing microalgae on the biofuels priority list: a review of the technological challenges

Abstract: Microalgae provide various potential advantages for biofuel production when compared with 'traditional' crops. Specifically, large-scale microalgal culture need not compete for arable land, while in theory their productivity is greater. In consequence, there has been resurgence in interest and a proliferation of algae fuel projects. However, while on a theoretical basis, microalgae may produce between 10-and 100-fold more oil per acre, such capacities have not been validated on a commercial scale. We criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
359
0
21

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 714 publications
(392 citation statements)
references
References 161 publications
1
359
0
21
Order By: Relevance
“…They are common in large-scale processes due to their nonspecific disruptive nature and high efficiencies (G€ unerken et al, 2015). Furthermore, they are most effective and energy efficient at cell concentrations of 100-200 g/L (Greenwell et al, 2010), which makes them suitable to treat concentrated algae streams without the need of a drying step. The most traditional mechanical microalgae pretreatments include bead milling, French press (high-pressure homogenization), ultrasonication, microwave techniques, and electric shock.…”
Section: Cell Disruption Effectiveness and Quality Bioproducts From Mmentioning
confidence: 99%
“…They are common in large-scale processes due to their nonspecific disruptive nature and high efficiencies (G€ unerken et al, 2015). Furthermore, they are most effective and energy efficient at cell concentrations of 100-200 g/L (Greenwell et al, 2010), which makes them suitable to treat concentrated algae streams without the need of a drying step. The most traditional mechanical microalgae pretreatments include bead milling, French press (high-pressure homogenization), ultrasonication, microwave techniques, and electric shock.…”
Section: Cell Disruption Effectiveness and Quality Bioproducts From Mmentioning
confidence: 99%
“…36,37 Porém, a produção de microalgas para produção de biocombustíveis ainda encontra gargalos tecnológicos dos quais depende a sua expansão à escala comercial, como: (a) dificuldades na logística de produção em larga escala; (b) dificuldades no uso de organismos geneticamente modificados em sistemas abertos; (c) alto custo na formulação do meio (micronutrientes); (d) complexidade no escalonamento industrial de fotobiorreatores; (e) alto custo de produção em sistemas heterotrófi-cos; (f) alta demanda energética para secagem e extração; e (g) alta acidez do material lipídico isolado. No entanto, é fato que muitos destes fatores não são limitantes quando o cultivo de microalgas está associado à produção de materiais de maior valor agregado, como pigmentos, antioxidantes, proteínas, ácidos graxos poli-insaturados, carboidratos funcionais e outras classes de substâncias biologicamente ativas.…”
Section: Biomassaunclassified
“…No entanto, é fato que muitos destes fatores não são limitantes quando o cultivo de microalgas está associado à produção de materiais de maior valor agregado, como pigmentos, antioxidantes, proteínas, ácidos graxos poli-insaturados, carboidratos funcionais e outras classes de substâncias biologicamente ativas. 37,38 O desenvolvimento de biocombustíveis avançados tem inspirado grande entusiasmo e potencial inovador em todos os setores e/ou competências associadas ao desenvolvimento científico e tecnoló-gico de nossa sociedade. O planejamento estratégico de instituições como a Agência Internacional de Energia (EIA) indica que as plantas atuais de produção de biocombustíveis já são capazes de deslocar 175 milhões de litros de derivados de petróleo anualmente e que esta estimativa deverá ser aumentada em incontáveis 1,9 bilhões de litros por ano ao serem consideradas as unidades que se encontram em construção e as que estão em estado avançado de planejamento e execução orçamentária.…”
Section: Biomassaunclassified
“…There appears to be considerably less research on the production of bioethanol than biodiesel, but bioethanol has been suggested as one of three top targets for future microalgal biofuel production (Gouveia 2011). The fermentation of microalgae has the potential advantage of exploiting the entire biomass, if an economic method of producing fermentable sugars from complex organic material is found.…”
Section: Microalgal Bioethanolmentioning
confidence: 99%
“…Intact cell walls hamper lipid recovery and the most effective methods of recovery are from disrupted microalgal cells (Greenwell et al 2010). Mechanical pressing is the industry standard for oil recovery from oilseeds for both food and biofuel production, but it is ineffective for microalgae (de Boer et al 2012).…”
Section: Biodiesel and Trans-esterificationmentioning
confidence: 99%